PDLLA scaffolds with Cu‐ and Zn‐doped bioactive glasses having multifunctional properties for bone regeneration. Issue 3 (7th November 2016) - Bejarano, Julian; Detsch, Rainer; Boccaccini, Aldo R.; Palza, Humberto
Abstract: Novel multifunctional scaffolds for bone regeneration can be developed by incorporation of bioactive glasses (BG) doped with therapeutic and antibacterial metal ions, such as copper (Cu) and zinc (Zn), into a biodegradable polymer. In this context, porous composite materials of biodegradable poly(d, l ‐lactide) (PDLLA) mixed with sol‐gel BG of chemical composition 60SiO2 ; 25CaO; 11Na2 O; and 4P2 O5 (mol %) doped with either 1 mol % of CuO or ZnO, and with both metals, were prepared. The cytocompatibility of the scaffolds on bone marrow stromal cells (ST‐2) depended on both, the amount of glass filler and the concentration of metal ion, as evaluated by lactate dehydrogenase (LDH) activity, cell viability (water‐soluble tetrazolium salt [WST‐8]), and by cell morphology (scanning electron microscopy [SEM]) tests. In particular, scaffolds having a filler content of 10 wt % showed the highest cytocompatibility. In addition, compared to the neat polymer, the scaffolds containing Cu promoted the angiogenesis marker (Vascular endothelial growth factor concentration) to a larger extent while scaffolds containing Zn increased the osteogenesis marker (specific alkaline phosphatase‐activity). Noteworthy, the scaffolds with both metal ions showed a combined effect on both properties. Cu‐ and Zn‐doped glasses also provided higher antibacterial capacity to PDLLA‐based scaffolds against methicillin‐resistant S. aureus bacteria than undoped glass. In combination, our results showed that by a proper addition of Cu‐ and Zn‐doped BG to a PDLLA matrix, multifunctional composite scaffolds with enhanced biological activity can be designed for bone tissue regeneration. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 746–756, 2017.